PRINCIPLES OF MARKET ECONOMY AND STRUCTURAL CHANGES IN THE RUSSIAN INSTRUMENT - V. N. Voronina (Модернизация, инновация, развитие, 2016)
This paper deals with result analysis of incoming of native instrument making into market economy. Reasons of dramatically worsening of many of enterprises condition and factors that are putting obstacles to its improvement are shown. Also variants of competiveness increasing ofRussian instruments are considered taking in account possible structure changes in its sphere.